Prinsip Kesantunan Berbahasa Dalam Acara Deddy’s Corner Trans TV - Wati, Reni; Hermaliza, Hermaliza (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
Princile Of Politeness Is Very Important In Everyday Life, It Is Not Uncommo For Misunderstandings To Occur Between The Speech And The Interlocutor. In Polite Speech, The Message Can Be Conveyed Well To The Interlocutor, Need To Pay Attention To The Principles Of Language Politeness. This Research Method Is Content Anwlysis Moethod. The Results Of This Study Are (1) Speech Which Incliteness Which Consists Of Wisdom Maxims 12 Utterances 3 Which Include Violations, (2) Speech That Includes The Principle Of Politeness, Which Consists Of The Maxim Of Generosity 2 Utterances, (3) Speech That Includes The Principle Of Politeness, Which Consists Of The Maxim Of Apprecion 3 Speech, (4) Speech That Includes The Princile Of Politeness, Which Consissts Of The Maxim Of Simplicity 0 Speech, (5) Speech That Includes The Principle Of Politeness, Which Consists Of Consensus Maxim 33 Utteances 2 Speech That Include Violation, (6) Speech That Includes The Principle Of Politeness, Whict Consists Of Sympathy Maxim 0 Speech